Sensitivity and Uncertainty Analysis on Reactivity for HEU and LEU Fuel Assemblies of Dalat Nuclear Research Reactor using Monte Carlo Code and ENDF/B-VII.0 and ENDF/B-VII.1 Nuclear Libraries - Thoi Nam, Chu; Tran Quang Linh, Le; Hartanto, Donny; Hoai Nam, Tran; Kien Cuong, Nguyen; Thanh Mai, Vu (VNU Journal of Science: Mathematics - Physics, 2022)
This paper presents the analysis of sensitivity and uncertainty for the infinite multiplication factor (k inf ) for the VVR-M2 typed HEU and LEU fuel assemblies of the Dalat nuclear research reactor (DNRR) using the MCNP6.1-Whisper1.1 code. Sensitivity calculations were performed for the ENDF/B-VII.0 and ENDF/B-VII.1 nuclear data libraries. In Whisper, the k eff uncertainty due to nuclear data was evaluated by the uncertainty propagation law using the sensitivities obtained by MCNP and the available covariance matrix. The most significant sensitivity coefficients in positive contribution are the coefficient total n and fission reaction of U-235, elastic scattering reaction of H-1 and inelastic scattering of thermal neutrons and in negative contribution are capture reactions of U-235, H-1, Al-27, U-238 and U-234 isotopes. The large discrepancy between sensitivities of elastic scattering reaction cross section of H-1 and inelastic scattering of thermal neutrons between two libraries are found because of the change in neutron spectra of HEU and LEU fuel assemblies using the two library versions. The uncertainty of the k inf from the ENDF/B-VII.0 nuclear library error for all isotopes was found to be significant (about 0.45% of reactivity effect) with the largest contribution from isotope U-235 contributions (about 0.3% to 0.40%).